2013 Kenya Enterprise Survey : Country Highlights - World Bank Group (Washington, DC, 2014)
The World Bank interviewed a representative sample of the private sector in 5 of the most active economic regions in Kenya. The sample consisted of 713 business establishments surveyed from January 2013 through February 2014. The enterprise survey covers several topics of the business environment as well as performance measures for each firm. This report presents following highlights from the survey: firms in Kenya exhibit low employment growth; more firms export compared to six years ago; and more days are needed compared to 2007 to clear customs for direct exports and import; firms in Kenya report an improvement in the use of financial service; losses due to crime have declined since 2007 but security expenses have become more burdensome; and one out of four firms in Kenya private sector consider informal competition as the biggest obstacle.